Ke Arah Pendidikan Nilai yang Efektif, Evaluasi dan Memperkuat Dimensi Pendidikan Nilai - Indriati Noor (Dinamika Ilmu, 2010)
Failure in education can create students with no sense of sensitivity, sensitivity which based on moral conscience, students with no sense of humanity and worse can spread moral degradation. Based on some evaluations, these phenomena were caused by several factors which among them are lack of harmony of synchronizing the teaching of values at home, school and community. Therefore some solutions are offered to strengthen the dimension of value (ethics) learning and teaching which among them are enriching the the educational material with moral values, empowering the sensibility of the students, creating the awareness among parents, educators and community members to collaborate in teaching values to students as well as giving a good examples in implementing moral values in the students life.